Effects of Duckweed Meal Supplementation in Un-processed and Extruded Diets on Performance and Economics of Broilers - Inderpal Singh; J.S. Lamba; R.S. Grewal; Udeybir Singh; Daljeet Kaur; Meera D. Ansal (Indian Journal of Animal Nutrition, 2023)
A study was conducted for nutritional evaluation of duckweed meal (DWM) as an alternate proteinsource in broilers. DWM supplemented in un-processed and extruded diets and performance of broilerswas observed. 256 IBL-80, day old commercial broiler chicks were randomly distributed into eighttreatments with, four replicates each. The treatments were divided into two dietary groups: Un-processeddietary group and Extruded dietary group. Both groups were having 4 treatments. Each replicatewas housing eight birds (8×4×8). Treatment T1 in both groups served as control treatment with 0%DWM, treatment T2, T3 and T4 were supplemented with 2, 4 and 6 % DWM. In both dietary groupssignificant differences for feed conversion ratio (FCR) was observed only during starter phase. In unprocesseddietary group best FCR, protein efficiency ratio (PER) and calorie efficiency ratio (CER) wasobserved for 2% duckweed meal supplemented group whereas in extrusion processed dietary group thebest FCR, PER and CER was observed for 4% duckweed treatment. The results indicated that duckweedmeal can be safely included in the broiler ration at 2 % level without treatment and at 4% level if used inextruded form.